ANALYSIS OF THE PRACTICAL EFFECTIVENESS OF DIGITAL MARKETING STRATEGIES IN TOURISM (Marketing Journal, 2025)
This paper assesses the effectiveness of digital marketing strategies in tourism enterprises, examining the relationships among the digital engagement index, brand awareness, customer retention, and conversion effectiveness. Using the Analytic Hierarchy Pr ocess (AHP) and parametric survival modeling (Weibull, Gompertz, Exponential), the study analyzes three destination clusters — ecotourism, cultural heritage sites, and urban hospitality firms. The findings reveal that adaptive personalization strategies ac hieve higher engagement, retention, and conversion rates than static -channel campaigns. Overall, the results confirm that digital engagement № 10-SON OKTA BR, 2025 -YIL 485 functions as a key mechanism of strategic adaptation and behavioral calibration within tourism marketing frameworks.
Keywords: digital marketing; tourism; AHP; survival model; personalization; digital engagement; conversion; retention